2021
DOI: 10.1002/lno.11981
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐deficient water zones in the Baltic Sea promote uncharacterized Hg methylating microorganisms in underlying sediments

Abstract: Human‐induced expansion of oxygen‐deficient zones can have dramatic impacts on marine systems and its resident biota. One example is the formation of the potent neurotoxic methylmercury (MeHg) that is mediated by microbial methylation of inorganic divalent Hg (HgII) under oxygen‐deficient conditions. A negative consequence of the expansion of oxygen‐deficient zones could be an increase in MeHg production due to shifts in microbial communities in favor of microorganisms methylating Hg. There is, however, limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Previous metagenomic studies have demonstrated the presence of hgc genes in oxygenated marine pelagic systems, suggesting a potentially important role of certain aerobic lineages, e.g., Nitrospina , in marine Hg II methylation. So far, less attention has been given to oxygen-deficient marine environments ,, where other Hg II -methylating lineages are expected to thrive. Consistent with other recent findings, our results based on the sequencing of metagenomes and metatranscriptomes (Datasheet 1B) from water samples demonstrated that redox conditions are a major factor controlling the presence and abundance of potential Hg II methylators in the central Baltic Sea water column (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous metagenomic studies have demonstrated the presence of hgc genes in oxygenated marine pelagic systems, suggesting a potentially important role of certain aerobic lineages, e.g., Nitrospina , in marine Hg II methylation. So far, less attention has been given to oxygen-deficient marine environments ,, where other Hg II -methylating lineages are expected to thrive. Consistent with other recent findings, our results based on the sequencing of metagenomes and metatranscriptomes (Datasheet 1B) from water samples demonstrated that redox conditions are a major factor controlling the presence and abundance of potential Hg II methylators in the central Baltic Sea water column (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, two recent studies based on the analysis of metagenomes from sulfate-enriched lakes revealed the presence of other hgc + microbial lineages including Kiritimatiellaeota (from PVC superphylum), Spirochaetes or Aminicenantes (Jones et al, 2019;Peterson et al, 2020). The contrasted diversity between water column and sediments was also recently observed in a brackish ecosystem, the Baltic Sea, in which hgc + Spirochaetes were predominant in sinking particles (Capo et al, 2020) but not in anoxic sediments (Capo et al, 2022a), while certain hgc + Desulfobacterota were abundant in both environments.…”
Section: Unveiling the Diversity Of Hg Methylators In Sinking Particl...mentioning
confidence: 81%
“…This process, also called Hg methylation, is mediated by microorganisms carrying hgcA and hgcB genes (hgc+ microorganisms) coding respectively for a corrinoid protein and a ferredoxin (Parks et al, 2013;Smith et al, 2015). The discovery of hgc genes opens avenues to unravel the diversity and distribution of putative Hg methylators in the environment in microbial groups recognized well to include Hg methylators (Desulfobacterota, Firmicutes, Methanomicrobia) (Gilmour et al, 2013;Podar et al, 2015) and in newly discovered groups such as Chloroflexota and PVC superphylum (McDaniel et al, 2020;Gionfriddo et al, 2020;Capo et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…The normalization of gene counts from environmental metagenomes and metatranscriptomes is a key aspect of works aiming to study the prevalence of certain microorganisms in specific environments (Pereira et al, 2018; Salazar et al, 2019; Pierella Karlusich et al, 2022). In hgcAB omics studies, the number of mapped reads and the coverage values of marker genes or housekeeping genes is usually used to normalize the coverage values of hgc genes (Lin et al, 2021; Vigneron et al, 2021; Tada et al, 2021; Capo et al, 2022). Tests here revealed that a wide range of contrasting normalization methods all provided reasonable abundance estimates that were significantly correlated with one another with the exception of genome equivalent values (Fig 4).…”
Section: Discussionmentioning
confidence: 99%